التناوب بين «أو» و «الواو» وأثره الدلالي - نصر، حسن رمادي غانم (جامعة الأزهر - كلية اللغة العربية بإيتاي البارود, 2021)
تؤدي كل من الأداة ""أو"" والواو"" معاني وظيفية يحددها السياق الذي ترد فيه، فكلاهما مفتقد لدلالته على معان معجمية، وكلاهما ذو دلالة تركيبية ووظيفة جوهرية في تناسق الجمل وترابطها، تتبين في البحث من خلال دراسة الصور الكلامية داخل جملها على المستوى التحليلي أو التركيبي. ومن هنا تبدو أهمية الموضوع كونه يناقش وسيلة من الوسائل التي يعتمد عليها النص اللغوي في ترابط فقراته، من خلال إقامة عنصر مقام عنصر آخر داخل التركيب، فيأخذ حكمه الوظيفي، أو يكتفى بأن ينوب عنه معنى أو لفظا. ولا يمكن الاستغناء عن عامل الربط داخل التركيب النحوي وبين أجزاء النص الواحد؛ إذ تتجسد جمالية النص اللغوي في تركيبه وبنيته المتسقة نحويا ودلاليا، والإخلال بالربط يؤدي إلى عدم فهم المعاني والدلالات في الجمل والنصوص. والبحث يعالج إنابة ""أو"" مناب ""الواو""، وإنابة "" الواو"" مناب "" أو"" في حالات لم يجمع عليها النحاة، بل قال بها بعضهم في مواضع معينة، من الآيات القرآنية، والقراءات القرآنية، والأحاديث النبوية، والأبيات الشعرية. ومجيء هذه الشواهد بتقديرات مختلفة جعل البحث يدرسها تحت باب الإنابة، مع ما تحتويه من معان أخرى لم ينكرها البحث، فالتراث لا يزال محتاجا إلى تقريب مادته وترتيبها، وبخاصة ما كان مبثوثا في مدونات التفسير، وهو ما يضفي على البحث طابع الأصالة، دون إغفال للدراسات المعاصرة والحديثة. ولأن البحث يركز على الجانب التطبيقي فقد آثر أن يسلك المنهج الوصفي في عملية التحرير والتوثيق والتحليل للتوصل إلى دلالة الحرفين المتناوبين، مبتعدا عن النزاع المثار في بعض شواهد البحث والاكتفاء بمعالجة هذا النزاع من خلال المقارنة بين أقوال العلماء ومقابلة حججهم، وترجيح رأي ما لظهوره وقوته، مبينا الأثر الذي خلفته دلالات هذا التناوب من نزاع لغوي وأحيانا شرعي، حسب الشواهد التي استطاع الباحث تجميعها لإثبات التناوب بين الأداتين ""أو"" و"" الواو""؛ لأن الفصل بينهما أمر لا يتفق والواقع اللغوي، بل إن في الفصل بينهما أثرا من آثار النظر العقلي المجرد الذي يجنح إلى التسهيل."
Both the tool “or” and the “waw” perform functional meanings determined by the context in which they are presented. Both lack lexical connotations, and both have a synthetic significance and a fundamental function in the consistency and coherence of sentences, which is evident in the research by studying the verbal images within their sentences at the analytical level or Synthetics. Hence, the importance of the topic appears as it discusses one of the means on which the linguistic text relies in the interconnection of its paragraphs, by establishing an element as the place of another element within the structure, so it takes its functional judgment, or is content to represent it with a meaning or a word. The linking factor within the syntactic structure and between parts of a single text cannot be dispensed with; As the aesthetic of the linguistic text is embodied in its syntax and structure consistent grammatically and semantically, and breaching the link leads to a lack of understanding of the meanings and connotations in the sentences and texts. The research deals with the assignment of the “waw” or the “subjunct” to the “waw”, and the assignment of the “waw” to the “munab” or “in cases that the grammarians did not unanimously agree upon, rather some of them said about them in certain places, from Qur’anic verses, Qur’anic readings, prophetic hadiths, and poetic verses. different estimates make the search studied under the door deputizing, with the content of other meanings deny not the search, the heritage is still in need of approximation of its substance and order, and especially what was Mbthotha in codes of interpretation, which gives the search stamp of authenticity, without losing sight of contemporary and modern studies. And because the research focuses on the application side, it has preferred to follow the descriptive approach in the process of editing, documentation and analysis to arrive at the significance of the two alternating letters, moving away from the conflict raised in some evidence of the research and contenting itself with dealing with this conflict by comparing the sayings of scholars and matching their arguments, and favoring an opinion for its appearance and strength. Indicating the effect of this alternation of language and sometimes legal conflict, according to the evidence that the researcher was able to collect to prove the alternation between the two tools ""or"" and ""waw""; Because the separation between them is not consistent with the linguistic reality. Rather, separating them has an effect of abstract mental consideration that tends to facilitate."
Keywords: اللغة العربية -- الدراسات اللغوية -- علم الدلالة